Predictors of Testis Cancer Mortality in Iran - Abedi, Amir Reza; Shojaeefar, Ehsan; Aliakbari, Fereshte; Ghanbari, Mohammad Ali; Hosseini, Jalil (Archives of Men’s Health, 2021)
Introduction: Testis cancer is a rare cancer that afflicts young men. although the incidence of testis cancer is increasing, the mortality rate is decreasing. This study examines the mortality of testicular cancer and its relationship with the human development index and its components in Iran during 2005-2015. Materials and Methods: Data of patients with testis cancer were collected from the Office of National Cancer Registry in the Ministry of Health and Medical Education (MOH&ME) during 2005-2015. An additional telephone survey was conducted by trained interviewers to collect data, including survival status, demographic characteristics, age of cancer diagnosis and other clinical profiles. Kaplan-Meier survival rates were calculated according to demographic characteristics, economic status, and residential area and socioeconomic status (SES). All the analyses were done using STATA software, version 14 (StataCorp. 2015). Results: From 2005 to 2015, 5886 testicular cancer cases were diagnosed among men in all age groups. Most patients (73.9%) were 15–49 years of age at the time of diagnosis, 26.1% were 50 years of age or older. Seminoma was diagnosed among 46.78% of the patients and non-seminoma among 42.28%. Factors which had impact on survival rate were age (P=0.001), tumor histology (P=0.02, hazard ratio=1.23[0.98-1.38]) and TNM stage (P=0.001, hazard ratio=1.2[0.92-1.28]). Patients who got married at the time of diagnosis more likely presented at earlier stages and had better overall testis cancer-specific survival than patients who were single, separated, widowed, or divorced (P=0.002, hazard ratio 1.27[1.09-1.49]). Testis cancer mortality rate was significantly higher in patients who did not graduate from high school and significantly higher in patients who were tenants (P=0.057, hazard ratio =1.132[0.996-1.28]). Conclusion: Testis cancer mortality is decreasing in Iran. Age, TNM stage and histology, and marital and economic status were factors influencing mortality rate.